Opioid weaning and pain management in postsurgical patients at the Toronto General Hospital Transitional Pain Service. Issue 1 (1st January 2018) - Clarke, Hance; Azargive, Saam; Montbriand, Janice; Nicholls, Judith; Sutherland, Ainsley; Valeeva, Liliya; Boulis, Sherif; McMillan, Kayla; Ladak, Salima S. J.; Ladha, Karim; Katznelson, Rita; McRae, Karen; et al.
ABSTRACT: Background: The perioperative period provides a critical window to address opioid use, particularly in patients with a history of chronic pain and presurgical opioid use. The Toronto General Hospital Transitional Pain Service (TPS) was developed to address the issues of pain and opioid use after surgery. Aims: To provide program evaluation results from the TPS at the Toronto General Hospital highlighting opioid weaning rates and pain management of opioid-naïve and opioid-experienced surgical patients. Methods: Two hundred fifty-one high-risk TPS patients were dichotomized preoperatively as opioid naïve or opioid experienced. Outcomes included pain, opioid consumption, weaning rates, and psychosocial/medical comorbidities. Results: Six months postoperatively, pain and function were significantly improved. Opioid-naïve and opioid-experienced patients reduced consumption by 69% and 44%, respectively. Forty-six percent and 26% weaned completely. Consumption at hospital discharge predicted weaning in opioid-naïve patients. Pain catastrophizing, neuropathy, and recreational drug use predicted weaning in opioid-experienced patients. Conclusions: The TPS enabled almost half of opioid-naïve patients and one in four opioid-experienced patients to wean. The TPS successfully targets perioperative opioid use in complex pain patients.